Analisis Unsur Komponen Fisik Terhadap Kemampuan Menyundul Bola Dalam Permainan Sepakbola Siswa SMA Negeri 2 Sinjai - Ahmad Adil (SPORTIVE: Journal Of Physical Education, Sport and Recreation, 2021)
This study aims (1) to determine the contribution of the elements of the physical components of explosive power with the ability to head the ball (2) to determine the contribution of the elements of the physical components of strength with the ability to head the ball (3) to determine the contribution of the elements of the physical components of flexibility with the ability to head the ball (4) to to know the contribution of the elements of the physical components of balance with the ability to head the ball (5) to know together the elements of the physical components of explosive power, strength, flexibility and balance with the ability to head the ball. The population in this study were students of SMA Negeri 2 Sinjai. By random sampling, a sample of 40 students. The data collection technique used a test to measure the physical components of explosive power, strength, flexibility and balance with the ability to head the ball. The data analysis technique used is correlation analysis. Based on the data analysis, the following results were obtained: (1) The contribution of the elements of the physical components of the explosive power with the ability to head the ball was 43.6%. (2) Contribution of the elements of the physical components of strength with the ability to head the ball by 39.0%. (3) The contribution of the physical components of back togok flexibility with the ability to head the ball by 39.3%. (4) The contribution of the physical components of balance with the ability to head the ball by 44.4%. (5) Jointly contribute to the physical components of the limb explosive power, abdominal muscle strength, backward flexibility and balance with the ability to head the ball by 50.4%